Coronavirus disease–2019 morbidity and mortality among health care workers in Uganda. (November 2022) - Ssetaba, Leoson Junior; Mirembe, Joy; Omega, Jotham; Okot, Jerom; Kiguli, Sarah; Nakwagala, Frederick Nelson; Bongomin, Felix
Background: Health care workers (HCWs) are at increased risk of acquiring coronavirus disease 2019 (COVID-19). This study aimed to determine and compare the morbidity and mortality rates due to COVID-19 among the HCWs and the general population (non-HCWs). Methods: We conducted a retrospective chart review. We accessed electronic database of participants admitted at Mulago National Referral Hospital COVID-19 Treatment Unit (CTU) between March 2020 and September 2021. Participants with missing occupations were excluded. Results: Of 594 eligible participants, 6.4% ( n = 38) were HCWs. Compared with non-HCWs, HCWs were much younger (48 versus 55 years, p = 0.020). The proportion of participants with severe disease (73.7% versus 77.6%, p = 0.442), who had not received COVID-19 vaccine (91.2% versus 94.7%, p = 0.423), mortality rate (44.7% versus 54.8%, p = 0.243) and the median length of hospitalization (6 versus 7 days, p = 0.913) were similar among HCWs and non-HCWs, respectively. A higher proportion of HCWs required oxygen therapy (24.3% versus 9.7%, p < 0.01). At admission, the presence of cough ( p = 0.723), breathlessness ( p = 0.722), fever ( p = 0.19), sore throat ( p = 0.133), comorbidities ( p = 0.403) and headache ( p = 0.162) were similar across groups. Rhinorrhoea was more common among HCWs (34.4% versus 16.6%, p = 0.017). Among HCWs, nurses had the highest morbidity (52.6%) and mortality (58.8%). Conclusion: The morbidity and mortality among HCWs in Uganda were substantial, with a low COVID-19 vaccination rate and a higher requirement for oxygen therapy despite a younger age.